2007
DOI: 10.1590/s1413-35552007000400013
|View full text |Cite
|
Sign up to set email alerts
|

A eficácia da terapia manual em indivíduos cefaleicos portadores e não-portadores de degeneração cervical: análise de seis casos

Abstract: Background: Tension-type headaches (TTH) are generally treated with prophylactic medication. With regard to Physical Therapy treatment, many types of procedures have been reported, ranging from electrotherapy and acupuncture to techniques such as cervical traction, vertebral mobilization, stretching and relaxation. Objective: To examine the evolution of six patients diagnosed with TTH who underwent a Physical Therapy treatment protocol consisting of manual therapy. Method: Six individuals were followed up (thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…(20) Thus it can be seen that the manual therapy maneuvering have a significant effect in relieving pain in muscles trigger points. …”
Section: Source: Research Datamentioning
confidence: 99%
See 1 more Smart Citation
“…(20) Thus it can be seen that the manual therapy maneuvering have a significant effect in relieving pain in muscles trigger points. …”
Section: Source: Research Datamentioning
confidence: 99%
“…(20) Physiotherapy has various manual techniques may provide pain relief, restoring structural and functional properties of the fabric, and may also affect the fluid flow, reducing the structural obstructions within the tissue.…”
Section: Source: Research Datamentioning
confidence: 99%
“…For this reason, are suggest studies with that population to promote greater support to speech therapy treatment. Inclusive, it was not found in literature studies on simultaneous treatment between Speech Therapy and Physical Therapy, which seems to be more effective, in view of the researched literature 10,29 .…”
Section: Acknowledgementmentioning
confidence: 92%
“…Thus, it is possible that the use of resonance tubes having one favored easier and relaxed phonation 3 . Study carried with 23 women without vocal complaints and ages between 23 and 40 years, who performed twice the exercises FingerKazoo and phonation with straw, showed reduction of the fundamental frequency after both exercises, Studies suggest a physical therapist therapy including electrotherapy and transcutaneous electrical nerve stimulation (TENS), light amplification by stimulated emission of radiation (laser) of low intensity, laser acupuncture, cryotherapy, among others 10,29 . A proven effective modality for normotensive cervical muscles is manual therapy with traction, massage, cervical manipulation and mobilization, associated or not to exercise, as well as passive stretching and/or resistive, isometric relaxation, assisted soft tissue mobilization (important in the treatment of muscle fascia), therapeutic exercises aiming to correct and balance muscle, diaphragm respiratory reeducation and therapy with craniocervical flexion 9,10,29 .…”
mentioning
confidence: 99%
“…In Vitoria/ES, it was observed that 69.9% of respondents with headache used common painkillers, among which sodium dipyrone (26.8%) and paracetamol (25.5%) 12 were the most frequently mentioned. In addition to pharmacological management, individuals may use non-pharmacological management, such as rest 13 , physiotherapy 14 and acupuncture 15 .…”
mentioning
confidence: 99%